2021
DOI: 10.1590/s2179-975x10719
|View full text |Cite
|
Sign up to set email alerts
|

Species-specific response of phytoplankton to zooplankton grazing in tropical eutrophic reservoirs

Abstract: Aim To test the hypothesis that zooplankton changes the structure of phytoplankton in tropical reservoirs by reducing the biomass of algal species susceptible to herbivory. Methods We experimentally evaluated the species-specific responses of phytoplankton to zooplankton within eutrophic reservoirs with different phytoplankton community structure in northeastern of Brazil. Water samples were collected from the subsurface in coastal regions of the Apipucos and Mundaú reservoirs in January/2012 and November/201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 60 publications
0
3
1
Order By: Relevance
“…In tests with the addition of cladocerans, we observed that the cyanobacterial biomass was significantly reduced from the fourth day and the green alga was stimulated on the eighth day, differing statistically from the control. This result differs from previous findings in the literature, where zooplankton are assumed to select the palatable food source in co-cultures, and thus stimulate cyanobacterial growth (Leitão et al, 2018;Severiano et al, 2021). However, in experimental studies, Guo and Xie (2006) found that populations of M. micrura pre-exposed to toxic strains M. aeruginosa may become more resistant to cyanobacteria metabolites compared to other large cladocerans, enabling the predation of cyanobacteria.…”
Section: Discussioncontrasting
confidence: 84%
See 2 more Smart Citations
“…In tests with the addition of cladocerans, we observed that the cyanobacterial biomass was significantly reduced from the fourth day and the green alga was stimulated on the eighth day, differing statistically from the control. This result differs from previous findings in the literature, where zooplankton are assumed to select the palatable food source in co-cultures, and thus stimulate cyanobacterial growth (Leitão et al, 2018;Severiano et al, 2021). However, in experimental studies, Guo and Xie (2006) found that populations of M. micrura pre-exposed to toxic strains M. aeruginosa may become more resistant to cyanobacteria metabolites compared to other large cladocerans, enabling the predation of cyanobacteria.…”
Section: Discussioncontrasting
confidence: 84%
“…Among the main bloom-forming genera, Microcystis stands out with wide geographical distribution and several microcystin-producing morphospecies (Harke et al, 2016;O'Neil et al, 2012;Wiegand & Pflugmacher, 2005). To control algal blooms, laboratory and in situ studies using aquatic plants (e.g., Amorim et al, 2019a;) and zooplankton organisms (e.g., Amorim et al, 2019b;Diniz et al, 2019;Severiano et al, 2018;Severiano et al, 2021) have been carried out in tropical regions, specifically in the Northeastern region of Brazil. In that region, the biomanipulation of fish to control eutrophication and phytoplankton blooms can show negative (Menezes et al, 2010), positive or no effects (e.g., Dantas et al, 2019;Okun et al, 2008).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Cynaphytes are associated with the production of toxins [7,8] and are often unigestible, indigestible, or nutritionally poor [9,10]. Many species of Chlorophytes are less palatable due to long splines and long processes [11]. In Lake Kariba, Limnothrissa miodon mainly feeds on zooplankton, especially the Cladoceran species Bosmina longirostris [12,13].…”
Section: Introductionmentioning
confidence: 99%